Evaluating pharmacist prescribing for minor ailments. (16th June 2014) - Mansell, Kerry; Bootsman, Nicole; Kuntz, Arlene; Taylor, Jeff
Abstract: Objectives: Saskatchewan is the second Canadian province to allow pharmacists to prescribe medications for minor ailments and the only province that remunerates for this activity. The aim of this project was to determine whether patients prescribed such treatment by a pharmacist symptomatically improve within a set time frame. Methods: Pharmacists were asked to hand a study-invitation card to anyone for whom they prescribed a medication for a minor ailment during the 1-year study period. Consenting participants contacted the study researchers directly and were subsequently instructed to complete an online questionnaire at the appropriate follow-up time. Key findings: Ninety pharmacies in Saskatchewan participated, accruing 125 participants. Cold sores were the most common minor ailment (34.4%), followed by insect bites (20%) and seasonal allergies (19.2%). Trust in pharmacists and convenience were the most common reasons for choosing a pharmacist over a physician, and 27.2% would have chosen a physician or emergency department if the minor ailment service were not available. The condition significantly/completely improved in 80.8%; only 4% experienced bothersome side effects. Satisfaction with the pharmacist and service was strong; only 5.6% felt a physician would have been more thorough. Conclusions: Participants were very satisfied with their symptomatic improvement and with the service in general, albeit for a small number of conditions. Participants reported getting better, and side effects were not a concern. These results are encouraging for pharmacists; however, a comparison of physician care with pharmacist care and unsupported self-care is required to truly know the benefit of pharmacist prescribing.